Effects of frequency and cutting height on dry-matter production, chemical composition, and regrowth of guinea grass - Favoretto, Vanildo; Tonini Júnior, Ricardo; Reis, Ricardo Andrade; Rodrigues, Luís Roberto de Andrade (Pesquisa Agropecuaria Brasileira, 2014)
This work was carried out at Faculdade de Ciências Agrárias e Veterinárias de Jaboticabal/ UNESP, São Paulo State, Brazil, in order to study the effect of two frequencies (35 and 42 days) and two cutting heights (15cm and 30cm from soil) on dry-matter production, chemical composition, and morphological and physiological characteristics of regrowth of guinea grass (Panicum maximum Jacq.) from January to April, 1984. Plants cut at intervals of 42 days showed higher percentage of decapitated tillers (53.70%), lower regrowth vigor (918.89kg DM/ha/21 days), and higher dry-matter production (12,652.67 kg/ha) than plants cut at 35 day Intervals. Regrowth vigor was better correlated with the percentage of decapitated tillers (r=- 0.60*) than with the levels of total nonstructural carbohydrates of stem basis (r = -0.04) and underground parts (r = -0.39). On the basis of dry-matter and crude protein productions, as well as chemical composition, guinea grass could be used from January to April at intervals of 42 days, independently of the cutting heights studies.